Equality and development - Elsenhans, Hartmut, 1941-; University of Dhaka. Centre for Social Studies (Dhaka, Bangladesh : Centre for Social Studies : Distributor, Dana Publishers, 1992)
With references to the Third World countries.
Includes bibliographical references (p. [288]-362).
Keywords: Economic development; Income distribution -- Developing countries; Income distribution; Capitalism -- Developing countries; Capitalism; Economic history; Developing countries -- Economic conditions